Good Practices in the Decannulation Process for people with Tracheostmy: Integrativa Literature Review - Oliveira Agostinho, Inês Margarida (2024)
Introduction: The progressive increase in individuals with tracheostomy and the delay in decannulation contribute to the rise in average hospitalization time, hence the need to understand and map the current knowledge on this subject arises. The success of early decannulation process provides greater autonomy for the individual, reduces hospitalization time, and facilitates a swifter return to home. However, the evidence on the topic of decannulation is scarce. In this regard, the guiding question of this study emerged: What are the best practices for implementing the decannulation process in a patient with a tracheostomy? The objectives established for this study are: (1) identification of the criteria for a successful decannulation; (2) identification of the stages of the decannulation process; (3) identification of the predictive factors for initiating decannulation; and (4) identification of the techniques that should be included in a rehabilitation program. Methodology: An integrative literature review was conducted, following the PRISMA methodology, to address the objectives: The search was conducted for the period between 2013 and 2023 in the databases available on the EBSCOHost® and PubMed® platforms. Results: The search included eleven articles that answered the initial questions. The categories of criteria for starting decannulation were: clinical stability, consciousness, ventilation and swallowing. With regard to the stages of decannulation, these fall into the categories covering airway patency, cuff deflation, phonation valve adaptation, occlusion training, cannula exchange, cough assessment and swallowing assessment and stimulation. Patient characteristics, comorbidities, consciousness, ventilation, and swallowing stand out as predictive indicators of decannulation. In addition, we obtained a comprehensive overview of the rehabilitation techniques adopted by multidisciplinary teams, such as muscle and respiratory strengthening, passive or active mobilization of limbs and early mobilization. Discussion: The results obtained in this review are in line with other authors and clinical practice. It is important to highlight that by considering these four aspects in the decannulation process: 1 - criteria for initiating decannulation, 2 - stages of decannulation, 3 - predictive indicators of decannulation success, and 4 - established rehabilitation program, it is possible to ensure decannulation with greater safety and success. Conclusion: The promotion of the decannulation process relies on systematic programs and protocols implemented by multidisciplinary teams to expedite the process. It is important to highlight the limited scientific evidence in this area, and the inherent limitations associated with its study.